Impacts of credit default swaps on volatility of the exchange rate in Turkey: The case of Euro - Muhsin Kar; Tayfur Bayat; Selim Kayhan (International Journal of Financial Studies, 2016)
In this study, we aim to investigate the impacts of credit default swaps (CDS) premium as a risk financial indicator on the fluctuations of value of the Turkish lira against the Euro. We try to answer the following questions: Is the CDS premium change among the drivers of EUR/TL exchange rate and what are the possible effects of CDS premium volatility on EUR/TL exchange rate stability in different conditions? In this regard, we developed a MS-VAR regime change model and asymmetric, frequency domain and rolling windows causality analysis methods. Results obtained from all tests imply that risk premium is partially a driver of the EUR/TL exchange rate between the years 2009 and 2015.
Keywords: F31; G10; 330; CDS premium; asymmetric causality; rolling windows causality